Cis–trans isomerization of dimethyl 2, 3-dibromofumarate. Issue 50 (14th November 2022) - Vo, Timothy H.; Korlacki, Rafał; Sinitskii, Alexander
Abstract : The bromination of dimethyl acetylenedicarboxylate initially results in mostly trans dimethyl 2, 3-dibromofumarate, which then converts into the more stable cis isomer. The trans -to- cis conversion is spontaneous and greatly accelerated by light. Abstract : The isomerization of dimethyl 2, 3-dibromofumarate in chloroform solutions was investigated by the combination of nuclear magnetic resonance (NMR) and density functional theory (DFT) calculations. The bromination of dimethyl acetylenedicarboxylate leading to dimethyl 2, 3-dibromofumarate produces the trans isomer initially, which however converts into the more stable cis isomer. The conversion from trans to cis is spontaneous and greatly accelerated by light.